Pretreatment neutrophil to lymphocyte ratio in determining the prognosis of head and neck cancer: a meta-analysis - Yu, Yalian (BMC Cancer, 2018)
BACKGROUND: Recent studies have reported a relationship between prognosis and neutrophil-to-lymphocyte ratio (NLR) in patients with head and neck cancer (HNC). As the results are still controversial, we conducted a meta-analysis of pretreatment NLR in peripheral blood and prognosis in HNC patients. METHODS: We retrieved articles from PubMed, Medline, Cochrane Library, Embase and Web of Science. A comparative analysis was conducted for the effect of pretreatment NLR in peripheral blood on overall survival (OS), progression-free survival, disease-free survival (DFS), disease-specific survival, metastasis-free survival, and recurrence-free survival of HNC patients. The analysis applied the criteria for systematic reviews described in the Cochrane Handbook and was conducted using hazard ratios (HRs) to estimate effect size, and calculated by Stata/SE version 13.0. RESULTS: The meta-analysis included eligible cohort studies (5475 cases). The OS data indicated increased mortality risk in HNC patients with a high NLR (HR = 1.84, 95% confidence interval (CI): 1.53–2.23; P < 0.001; heterogeneity, I(2) = 37.2%, P = 0.074). Analysis of subgroups stratified by NLR cutoff values revealed increased mortality risk and significantly shorter DFS in patients with high NLR compared to those with low NLR (HR = 2.18, 95% CI: 1.46–3.24; P < 0.001). Patients with high NLR had a higher probability of tumor recurrence after treatment than those with low NLR (HR = 1.63, 95% CI: 1.09–2.45; P = 0.017; heterogeneity, I(2) = 68.7%; P = 0.022). The probability of distant metastasis following treatment was greater in patients with high compared with low NLR (HR = 1.92, 95% CI: 1.36–2.72; P < 0.001; heterogeneity, I(2) = 0.0%; P = 0.614). Funnel plots of the meta-analysis results were stable, as shown by sensitivity analysis. No publication bias was detected by the Egger test (P = 0.135). CONCLUSIONS: HNC patients with elevated pretreatment NLR in peripheral blood have poor prognosis and are prone to local invasion and distant metastasis. NLR values are easily obtained from routinely collected blood samples and could assist clinicians to determine prognosis of HNC patients.